Chronic Kidney Disease Stage and Cardiovascular and Mortality Events Among Older Adults: The SPRINT Trial (2024)
Rationale & Objective: The risk implications of the Kidney Disease: Improving Global Outcomes (KDIGO) CKD classification in older adults are controversial. We evaluated the risk of adverse outcomes in this population across categories of estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR). Study Design: Prospective cohort. Settings & Participants: 2509 participants aged ≥75 years in the Systolic Blood Pressure Intervention Trial (SPRINT). Exposures: KDIGO eGFR and UACR categories. We combined KDIGO categories G1 and G2, G3b and G4, as well as A2 and A3. Outcomes: Primary SPRINT outcome (composite of myocardial infarction, other acute coronary syndromes, stroke, heart failure, or death from cardiovascular causes), and all-cause death. Analytical Approach: Multivariable Cox proportional hazard models. Results: Mean age was 79.8 years, 37.4% were female, mean eGFR was 64.0 ml/min/1.73 m2, and median UACR 13.1 mg/g. In multivariable Cox proportional hazard analysis, compared with participants with eGFR ≥60 ml/min/1.73 m2 and UACR <30 mg/g, there was no statistically significant difference in the risk of the primary outcome among participants with eGFR 45-59 or 15-44 ml/min/1.73 m2 and UACR <30 mg/g. However, those with eGFR 45-59 or 15-44 ml/min/1.73 m2 and UACR ≥30 mg/g had higher risk of the primary outcome (HR [95% CI], 1.97 [1.27, 3.04] and 3.32 [2.23, 4.93], respectively). The risk for all-cause death was higher for each category of abnormal eGFR and UACR, with the highest risk observed among those with eGFR 15-44 ml/min/1.73 m2 and UACR ≥30 mg/g (3.34 [2.05, 5.44]). Limitations: Individuals with diabetes and urine protein >1 g/day were excluded from SPRINT. Conclusion: Among older adults SPRINT participants, low eGFR without albuminuria was associated with higher mortality but not with increased risk of cardiovascular events. Additional studies are needed to evaluate an adapted CKD stage-based risk stratification for older adults.